Sistem Sortir Barang Otomatis Berbasis Arduino Dengan Sensor Warna Dan Monitoring Via Android - T.W. Wisjhnuadji; Arsanto Narendro; Pribadi Wicaksono (LPPM, 2020)
The Arduino-based sorting system is equipped with a color sensor and the monitoring of the number of goods via Android is a series of tools that serves to ease the work process of sorting goods by color manually at certain industrial companies. The method used to realize the problem above is by making a prototype of the sorting tool based on color automatically and monitoring the results of the sum of the items as connecting information from the device to Android. The tool is equipped with a TCS3200 color sensor as a color detector, an infrared sensor as an object counter, a DC motor and conveyor as a driving medium, a Servo motor as a sorting media, Arduino as a control media, and ESP8266 as a communication media and Android as a monitoring media. The results of test have been carried out on the prototype of this system, and are able to provide results in accordance with the design specifications of the tool.Keywords: arduino, android, sensor warna, sensor infrared, motor DC, motor servo, ESP8266